1993
DOI: 10.1017/s0022029900027916
|View full text |Cite
|
Sign up to set email alerts
|

Toxin production byBacillus cereusin dairy products

Abstract: SummarySpores of a known toxigenic and psychrotrophic dairy isolate ofBacillus cereus(HRM 44) were unable to grow and produce diarrhoeagenic toxin at 6 °C in creams and dairy-based products. These findings suggest that the production ofB. cereusdiarrhoeagenic toxin is unlikely to occur in creams and dairy-based products maintained within the cold chain. Growth and toxin production were readily demonstrated in creams and some desserts stored at 21 °C. Growth in creams was associated with obvious spoilage. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…() have reported the absence of cytotoxic activity of raw milk isolates exhibiting a high spoilage potential. Sutherland () noticed that the spoilage of flavoured desserts was not always obvious at 21°C before significant growth of B. cereus group bacteria, while toxin production was systematically observed. According to the present study, the isolates appearing as the most pathogenic at medium temperature appear as the least spoiling at refrigerated temperature (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…() have reported the absence of cytotoxic activity of raw milk isolates exhibiting a high spoilage potential. Sutherland () noticed that the spoilage of flavoured desserts was not always obvious at 21°C before significant growth of B. cereus group bacteria, while toxin production was systematically observed. According to the present study, the isolates appearing as the most pathogenic at medium temperature appear as the least spoiling at refrigerated temperature (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…from the food chain is not possible, and the only recognised control method involves maintaining a cold temperature throughout the processing, manufacture and storage stages. It had been reported that toxogenic B. cereus strains could affect the constituents in dairy desserts during toxin formation [12] . B. cereus causes problems by degrading dairy products, creating off-flavours, sweet curdling and bitter cream because of the production of proteinase, lipase and phospholipases, and it endangers public health through food contamination [13,14] .…”
Section: Determination Of Enterotoxigenic Gene Profiles Of Bacillus Cmentioning
confidence: 99%
“…Fluid accumulation in ligated rabbit ileal loops and vascular permeability reactions have been used routinely to detect enterotoxin (Kramer and Gilbert 1989). Vero cells (Granum et al 1993), Chinese hamster ovary (CHO) cells (Buchanan and Schultz 1992), and human embryonic lung (HEL) cells (Christiansson 1989(Christiansson , 1993Christiansson et al 1989) have been used in cell culture assays for enterotoxin, but neutralization of enterotoxin by specific antisera may be needed, as the lecithinase and haemolysin of B. cereus are cytopathic for some cell cultures (Sutherland 1993).…”
Section: Bacillus Cereus Emetic Toxin and Enterotoxinmentioning
confidence: 99%